Spotlight on science and literature at the corners of southwestern Algeria in the modern era - Moussaoui, Medjdoub (Journal of Human Sciences, 2023)
This article sheds light on the various religious sciences and literary arts that were taught in the corners of southwestern Algeria in the modern era and the most important classifications that were written in this field, as local sources mention to us that these angles have mostly succeeded in the formation and graduation of a significant number of sheikhs, teachers and students The competent, who had a great role in continuing the message of Science and the prosperity of the cultural movement in this era with their various scientific and intellectual contributions in writing and writing.